OP23 CKD-506, a novel histone deacetylase (HDAC) 6 inhibitor, ameliorates colitis in various animal models. (25th January 2019) - Shin, J; Ha, N; Bae, D; Suh, D-h; Baek, J-y; Jun, J H; Lee, Y J; Choi, Y I; Ryu, K H; Youn, G S; Park, J; Lee, S-M; et al.
Abstract: Background: Inhibition of HDAC6 has been proposed beneficial and therapeutic effects in inflammatory bowel disease. CKD-506, an oral selective HDAC6 inhibitor, had completed phase I clinical study and is being investigated for rheumatoid arthritis in phase II clinical study. Herein, we verified the therapeutic effect of CKD-506 in various colitis animal models and identified its underlying molecular mechanisms. Methods: HDAC6 expression was assessed in colon tissue of healthy individual and patients with Crohn's disease and ulcerative colitis by real-time RT-PCR and immunohistochemistry. Macrophages with HDAC6 overexpression were used for mechanism studies. DSS-, TNBS-, Piroxicam (IL-10 −/− )-, and adaptive T-cell transfer (RAG1 −/− )-mediated colitis animal models were used to check the efficacy of CKD-506. Colitis animals were treated with 1 to 100 mg/kg of CKD-506 and analysed disease activity indexes such as body weight, and colon length, and cytokines in serum, colon tissue, and lamina propria mononuclear cells (LPMC). Results: HDAC6 was overexpressed in colon tissue of patients with Crohn's disease and ulcerative colitis. In vitro, HDAC6 overexpression by pDNA strongly induced the production of various inflammatory mediators, especially TNFa, IL-6, IP-10, and ROS production from macrophages. However, CKD-506 inhibited HDAC6-mediated inflammatory responses in macrophages through NF-kB and AP-1. In vivo, CKD-506 strongly inhibited disease activity indexes in DSS-, TNBS-, Piroxicam- (IL-10 −/− )-, and adaptive T-cell transfer-mediated colitis. In acute colitis models, CKD-506 inhibited IL-6 and TNFa expression in colon tissue of DSS-induced colitis and also inhibited ICAM-1, VCAM-1, and IP-10 expression in colon tissue of TNBS-induced colitis model. In addition, CKD-506 inhibited Ik-B phosphorylation, IL-6, and TNFa expression in colon tissue and mononuclear cells of lamina propria in Piroxicam-induced colitis of IL-10 −/− mice. Moreover, CKD-506 inhibited various inflammatory cytokines in serum as well as in colon tissue of T-cell adaptive transfer colitis of RAG −/− mice. Conclusions: These data provide insight that inhibition of HDAC6 by CKD-506 has therapeutic effect in colitis animal models. Therefore, CKD-506 may beneficial effect in patients with Crohn's disease and ulcerative colitis.